Retarding field energy analyzers for ion temperature measurements in the boundary plasmas of the tokamak ISTTOK and TJ-II stellarator - Nedzelskiy, I.S.; Silva, C.; Fernandes, H.; Hidalgo, C. (Вопросы атомной науки и техники, 2009)
The retarding field energy analyzer (RFEA) remains the more reliable diagnostic to measure the ion temperature in the boundary plasmas of magnetic fusion devices. A compact, simple design RFEA have been developed for investigations on the tokamak ISTTOK and TJ-II stellarator. More recently a five-channel RFEA has been successfully tested allowing the simultaneous measurement of the ion temperature profile. The conditions of the RFEA operation in poor alignment along magnetic field are considered.